2009
DOI: 10.4067/s0717-95022009000100039
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Morphometric Study of the Mental Foramen on the M-CP-18 Jiachenjiang Point

Abstract: SUMMARY:The purpose of this work was to study the morphology and morphometry of the mental foramen (MF), as well as to evaluate its morphological configuration; in addition to taking measures of its localization using as a parameter the distances of the foramen to the inferior border of the mandible and at the alveolar ridge. 80 dry mandibles were analyzed using the test of Qui-square and T test, with 5% of significance. Its average distance, on the right side, at the inferior edge of the mandible (IEM) was of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
3
15
3
1
Order By: Relevance
“…In the present study, predominant shape observed is round both on right (94%) and left sides (87%) which is similar to study conducted by Al-Khateeb et al [13] However Oliveira Junior et al [14] reported round shape only in 26.2% and 28.7% of mandibles on right and left sides respectively and in rest of mandibles, oval shape was observed 73.8% on right side and 71.3% on left side.…”
Section: Shape Of Mfsupporting
confidence: 90%
“…In the present study, predominant shape observed is round both on right (94%) and left sides (87%) which is similar to study conducted by Al-Khateeb et al [13] However Oliveira Junior et al [14] reported round shape only in 26.2% and 28.7% of mandibles on right and left sides respectively and in rest of mandibles, oval shape was observed 73.8% on right side and 71.3% on left side.…”
Section: Shape Of Mfsupporting
confidence: 90%
“…The numerical values in parentheses indicate ranges. reported in most previous studies [6,15]. However, Sankar [21] found that the round MF form was most common in an Indian population.…”
Section: Discussionmentioning
confidence: 88%
“…The same position was also observed to be most common in Saudi [28], Nigerian [29], Kenyan [17], Sri Lankan [6], and Kurdish [7] populations. However, other studies suggested that most MF were located between the first and second premolars [8,15,30]. Thus, the location of the MF appears to show racial differences [31].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations